ANALISIS STRUKTUR, PERILAKU, DAN KINERJA PEMASARAN KENTANG GRANOLA DI KECAMATAN PANGALENGAN, KABUPATEN BANDUNG, JAWA BARAT - Vela Rostwentivaivi Sinaga; Anna Fariyanti; Netti Tinaprilla (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2014)
High number of production and vast planting area make Pengalengan as granola potato production center of Bandung Regency. Problems faced by potato farmers of the area are price volatility, limited market information, and middleman controlled market. The purpose of this study is to analyze granola potatoes market structure, conduct, and performance at Pangalengan. The methods used are market concentration and market entry and exit barriers to analyze market structure; marketing function (exchange, physical and facilities) to analyze market conduct; and farmer share and marketing margin to analyze market performance. The result shows granola potato market has nine marketing channel, oligopsony market, farmer position as price taker and middleman caused barrier to entry and relatively efficient market performance with an average value of 27,64 percent and an average farmer share of 72,36 percent.